Angka Kejadian dan Karakteristik Klinis Pasien Infeksi Jamur Invasif di RSUP Dr. Hasan Sadikin Tahun 2020 – 2022 - Alessandro, Ariella; Fauziah, Nisa; Megantara, Imam; Wisaksana, Rudi; Dewi, Intan Mauli Warma (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Invasive fungal infection (IFI) is increasingly common in patients at risk, especially those with impaired immune response. In Indonesia, there is currently a low prevalence of IFI which may be influenced by challenges in diagnosis. This study aimed to determine the prevalence and clinical characteristics of IFI patients in Dr. Hasan Sadikin Hospital in Bandung, Indonesia. Methods. This cross-sectional study was conducted at Dr. Hasan Sadikin Hospital. Data were collected using medical records of IFI patients diagnosed between 2020 and 2022 which were selected using total sampling method. Demographic data, clinical symptoms, radiological appearance, and laboratory results were recorded. Results. The prevalence of IFI in Dr. Hasan Sadikin Hospital between 2020 and 2022 was 0,04% (40 per 100,000 patients). The most common cause of invasive fungal infection was Cryptococcus spp. and Candida spp. Fever and loss of consciousness were the two most common signs and symptoms found in this study. HIV/AIDS was present in 51,4% of cases. The diagnostic test was mostly done with cryptococcal antigen (CrAg) examination. Lung involvement was common, appearing as consolidation, infiltration, and ground glass opacity in the lungs. The mortality rate of IFI patients was 51,4%. Conclusions. The prevalence of IFI in Dr. Hasan Sadikin Hospital was quite low, with HIV/AIDS as the most common risk factor. However, there was a high mortality rate found this study is high. Thus, timely diagnosis and antifungal treatment induction should be considered to improve the outcome of invasive fungal infection patients.